Efektivitas Layanan Arsip dalam Pembuatan Salinan Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Kubu Raya - Sandi Yudha, Eka Nesti Ardian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the performance of the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Kubu Raya Regency in efforts to increase regional investment. The research method used is descriptive qualitative analysis with a case study approach. Data were obtained through in-depth interviews, observations, and documentation studies. The results show that DPMPTSP Kubu Raya Regency has implemented various service innovations that have successfully increased the efficiency of the licensing process and investment realization. The implementation of the Online Single Submission (OSS) system and the